2011
DOI: 10.1124/jpet.111.183525
|View full text |Cite
|
Sign up to set email alerts
|

Lorcaserin, a 5-HT2C Agonist, Decreases Nicotine Self-Administration in Female Rats

Abstract: Lorcaserin, a selective 5-hydroxytryptamine 2C (5-HT 2C ) agonist, has been shown to facilitate weight loss in obese populations. It was assessed for its efficacy in reducing nicotine self-administration in young adult female Sprague-Dawley rats. The effect of short-term doses (subcutaneous) on nicotine selfadministration (0.03 mg/kg per infusion) with a fixed ratio 1 schedule was assessed in 3-h sessions. Short-term lorcaserin doses (0.3125-20 mg/kg) were administered in a counterbalanced order. Significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 13 publications
7
76
1
1
Order By: Relevance
“…In clinical studies, lorcaserin is well tolerated and decreases food intake and body weight (Smith et al, 2009(Smith et al, , 2010Chan et al, 2013;Aronne et al, 2014) at doses that have low potential for producing heart valve disease (Weissman et al, 2013) or abuse (Shram et al, 2011), effects commonly associated with 5-HT 2B and 5-HT 2A receptor agonists, respectively (Nichols, 2004;Hutcheson et al, 2011). In addition to preclinical studies demonstrating that lorcaserin decreases food intake and body weight (Smith et al, 2008;Thomsen et al, 2008;Higgins et al, 2013b;Grottick et al, 2015), lorcaserin is also shown to decrease nicotine selfadministration and the reinstatement of responding for nicotine in rats (Levin et al, 2011;Higgins et al, 2012Higgins et al, , 2013b.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical studies, lorcaserin is well tolerated and decreases food intake and body weight (Smith et al, 2009(Smith et al, , 2010Chan et al, 2013;Aronne et al, 2014) at doses that have low potential for producing heart valve disease (Weissman et al, 2013) or abuse (Shram et al, 2011), effects commonly associated with 5-HT 2B and 5-HT 2A receptor agonists, respectively (Nichols, 2004;Hutcheson et al, 2011). In addition to preclinical studies demonstrating that lorcaserin decreases food intake and body weight (Smith et al, 2008;Thomsen et al, 2008;Higgins et al, 2013b;Grottick et al, 2015), lorcaserin is also shown to decrease nicotine selfadministration and the reinstatement of responding for nicotine in rats (Levin et al, 2011;Higgins et al, 2012Higgins et al, , 2013b.…”
Section: Introductionmentioning
confidence: 99%
“…un estudio clínico reciente en fase ii demostró que la lorcaserina se asoció con una tasa mayor en el cese del tabaquismo sumado a una reducción en el peso corporal comparado con placebo 8 . Por otra parte, estudios en animales han demostrado que lorcaserina reduce la autoadministración de nicotina 9 . El uso de lorcaserina se asocia a una baja de peso promedio de 3 kg en pacientes con peso cercano a 100 kg, o una reducción en el iMC de 1,2 kg/m 2 en pacientes con iMC basal de 36 kg/ m 2 .…”
Section: Lorcaserinaunclassified
“…In preclinical studies, lorcaserin was found to decrease nicotine self-administration and nicotineenhanced responding for conditioned reinforcement in rats [266][267][268]. A recent phase 2 clinical trial found that lorcaserin was associated with a significantly higher continuous quit rate compared with placebo.…”
Section: Relative Efficacymentioning
confidence: 99%
“…In addition, lorcaserin used alone or combination with varenlicine may be a novel agent for smoking cessation given that 5-HT systems play key roles in the action of nicotine [266].…”
Section: Lorcaserinmentioning
confidence: 99%